Gas permeation models in mixed matrix membranes for gas separation - Rafiq, S. (Trans Tech Publications Ltd, 2014)
Various theoretical models on CO2 permeation were discussed that included Maxwell model, Bruggeman model, Lewis-Nielson model and Pal model. These models were used for comparing the relative permeance of CO2 with the previously published experimental data on silica nanoparticles filled polysulfone/polyimide (PSF/PI) mixed matrix membranes (MMMs). The results showed that the deviation was in the increasing order: Lewis-Nielsen model< Maxwell model< Pal model< Bruggeman model. All these models assumed that the fillers are spherical in shape. A scanning electron microscope (SEM) cross-sectional image indicated that the silica particles were prolate ellipsoids that were dispersed in the matrix. To investigate the prolate effect, the Maxwell- Wagner-Sillar (MWS) model was employed. The evaluation from cross-sectional image of the membrane structure indicated that the shape factor along z-direction gave a minimum deviation of 17.52-20.10 at 2-10 bar feed pressure respectively. Â© (2014) Trans Tech Publications, Switzerland.